Komunikativna kompetentnost - Kuhar, Metka (Javnost (Ljubljana), 2006)
In the article the theoretical-empirical and lay conceptualizations of communicative competence are compared. In the first part different conceptions of communicative competence are analysed. The conceptions are divided into two groups. In the first group communicative competence is predominantly defined as cognitive phenomenon and the focus is on cognitive, emotional and behavioural strategies and skills that predict communicative behaviour. The second group of theories and studies focuses on contextual sociolinguistic characteristics. They deal with speech acts and communication events in particular speech communities. Further the results of qualitative study on a sample of 204 students are presented. The comparative method (Glaser in Strauss 1979) yielded the following dimensions of communicative competence: 1) intellectual, 2) linguistic, 3) nonverbal, 4) situational, 5) focus on the other, 6) focus on self, 7) personal characteristics of communicator, 8) skills. The students have exposed many dimensions of communicative competence that are significantly different from established definitions. We suggest, on the one hand, that measurement instruments for communicative competence should be adjusted to concrete communication situation: on the other hand, we propose dialogic communicative competence as an attempt towards a more universal definition of communicative competence in the modern plural society.
Keywords: communication; komuniciranje; sociološke teorije; sociolinguistics; sociolingvistika; kognitivna lingvistika